Ineffective Health Management for Family Hypertension Care in Sumberjambe Community Health Center - Ramadhani, Nurhafidin; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2024)
Background: The family is the smallest social unit in society that plays a role in reducing the risk of disease and increasing health status. Ineffective family health management occurs when the pattern of handling problems is not satisfactory enough to restore the health condition of family members. Purpose: This scientific work aims to identify healthcare problems with hypertensive families and provide interventions for families. Methods: This study used a case study method that described the health management of three families with hypertension in the Sumberjamber-Jember Health Center work area, then interventions were given in the form of health education, anti-hypertension exercises, and herbal cucumber juice therapy for three consecutive days. Results: After nursing care, it was obtained that there was an increase in knowledge related to hypertension seen from the pre-post test value, there was a change in blood pressure at 10 minutes before and after the anti-hypertension exercise, and no decrease in blood pressure was found after giving cucumber extract herbal therapy. Conclusion: Nurses can implement health education interventions, physical activity, and additional therapy in solving ineffective family health management problems.